Green and Rapid Preparation of Fluorosilicone Rubber Foam Materials with Tunable Chemical Resistance for Efficient Oil–Water Separation - Hu, Wan-Jun; Xia, Qiao-Qi; Pan, Hong-Tao; Chen, Hai-Yang; Qu, Yong-Xiang; Chen, Zuan-Yu; Zhang, Guo-Dong; Zhao, Li; Gong, Li-Xiu; Xue, Chang-Guo; Tang, Long-Cheng (Polymers, 2022)
Polydimethylsiloxane (PDMS) foam materials with lightweight, excellent oil resistance and mechanical flexibility are highly needed for various practical applications in aerospace, transportation, and oil/water separation. However, traditional PDMS foam materials usually present poor chemical resistance and easily swell in various solvents, which greatly limits their potential application. Herein, novel fluorosilicone rubber foam (FSiRF) materials with different contents of trifluoropropyl lateral groups were designed and fabricated by a green (no solvents used) and rapid (<10 min foaming process) foaming/crosslinking approach at ambient temperature. Typically, vinyl-terminated poly(dimethyl-co-methyltrifluoropropyl) siloxanes with different fluorine contents of 0–50 mol% were obtained through ring-opening polymerization to effectively adjust the chemical resistance of the FSiRFs. Notably, the optimized FSiRF samples exhibit lightweight (~0.25 g/cm−3), excellent hydrophobicity/oleophilicity (WCA > 120°), reliable mechanical flexibility (complete recovery ability after stretching of 130% strain or compressing of >60%), and improved chemical resistance and structural stability in various solvents, making them promising candidates for efficient and continuous oil–water separation. This work provides an innovative concept to design and prepare advanced fluorosilicone rubber foam materials with excellent chemical resistance for potential oil–water separation application.